S16-4: Supporting the Long-Term Maintenance of Physical Activity for People Who Live With Severe Mental Ill Health (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Increasing physical activity could reduce the mortality gap experienced by people with serious mental illness (SMI). Physical activity must be undertaken regularly over an extended period to offer maximal benefits. This study provides insights into supporting continued activity for people with SMI.Methods: An international sample of stakeholders (n = 19) were consulted. In-depth, semi-structured interviews were undertaken with: 1) peer physical activity practitioners (n = 5) who were involved in the design and delivery of physical activity programmes for people with SMI, 2) physical activity leaders (n = 3), and 3) people with SMI who participated in these physical activity programmes (n = 25). Data were analysed using framework analysis.Results: Group activities designed specifically for people with SMI and incorporating structured socialisation opportunities will facilitate adherence. Gradual exposure to the group activities is needed, with one-on-one support incorporating personalised goals made available to participants. Socialisation opportunities require meticulous planning by the practitioners to curate social interactions that encourage participant bonding carefully.Qualities of practitioners deemed essential for adherence included ‘soft skills’, which encompass a wide range of interpersonal skills. These include fostering warm connections (i.e. demonstrating kindness and warmth towards group members), accepting, being non-judgemental, looking past faults, being genuine, encouraging, and flexible, and cultivating mutual respect). Not putting pressure on participants and encouraging autonomous motivation, tailoring sessions to participants’ mental and physical health capabilities and needs were also imperative.Our findings underscore the importance of mutual compatibility between the participant and the practitioner in the success of physical activity programmes for individuals with SMI. Therefore, providing participants with a choice of practitioners with whom they feel compatible with is a key factor in ensuring their comfort and engagement.Conclusions: Ensuring that programmes are adequately planned, supported, and resourced will be critical for their ability to foster prolonged participation.The qualities of the practitioners delivering these programmes and the ability to work beyond their professional roles’ limitations were identified as essential. This suggests a need for changes at the organisational and system levels to support ongoing participation in physical activity.Support/Funding Source: The NIHR Clinical Research Network.